The Effect of Community Satisfaction on Public Service Quality at Tawiri Health Center, Ambon City - Huwae, Getlin Triniti; Lesnussa, Johny U.; Renyut, Selvi F. G. (JIMAD : Jurnal Ilmiah Multidisiplin, 2025)
This study aims to analyze the influence of community satisfaction levels on the quality of public health services at the Tawiri Health Center, Teluk Ambon District, Ambon City. Using a quantitative research approach, the study collected and analyzed data to determine the relationship between satisfaction variables and service quality. The results showed that the community satisfaction variable has a positive and significant influence on the quality of services. This is supported by the significance value of 0.024, which is smaller than the standard value of 0.05, and the t-count of 71.153, which is greater than the t-table value of 1.676. These findings indicate that as community satisfaction increases, the perceived service quality also improves. The study concludes that good service quality leads to higher satisfaction among patients, increasing public trust in health services. Therefore, efforts to enhance patient satisfaction are crucial in improving service quality in public health facilities.